2019
DOI: 10.1016/j.actbio.2019.01.044
|View full text |Cite
|
Sign up to set email alerts
|

Porous PolyHIPE microspheres for protein delivery from an injectable bone graft

Abstract: Delivery of osteoinductive factors such as bone morphogenetic protein 2 (BMP-2) has emerged as a prominent strategy to improve regeneration in bone grafting procedures. However, it remains challenging to identify a carrier that provides the requisite loading efficiency and release kinetics without compromising the mechanical properties of the bone graft. Previously, we reported on porous, polymerized high internal phase emulsion (polyHIPE) microspheres fabricated using controlled fluidics. Uniquely, this solve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 74 publications
(90 reference statements)
0
39
0
Order By: Relevance
“…They reported that while the encapsulation efficiency of their system was up to 73%, but this efficiency reduced to as low as 15% in the processes which require purification. In the follow-up study from the same group, they have shown the sustained release of BMP-2 in at least 14 days, and the retention of bioactivity was confirmed by osteogenic differentiation of osteoblasts cultured on these microspheres (Whitely et al, 2019).…”
Section: Drug-releasing Polyhipesmentioning
confidence: 79%
See 1 more Smart Citation
“…They reported that while the encapsulation efficiency of their system was up to 73%, but this efficiency reduced to as low as 15% in the processes which require purification. In the follow-up study from the same group, they have shown the sustained release of BMP-2 in at least 14 days, and the retention of bioactivity was confirmed by osteogenic differentiation of osteoblasts cultured on these microspheres (Whitely et al, 2019).…”
Section: Drug-releasing Polyhipesmentioning
confidence: 79%
“…Microporous PolyHIPE particles can be applied to the defect site by injecting and used as substrates for controlled drug delivery ( Moglia et al, 2014a ; Whitely et al, 2019 ). They can be created using multiphasic emulsion systems that are mostly water-in-oil-in-water (w/o/w) emulsions.…”
Section: Development Of the Emulsion Templated Scaffoldsmentioning
confidence: 99%
“…Unlike styrene-based polyHIPEs, acrylate-based ones are degradable to a certain extent and have a larger selection of monomers that can be used in the polymerisation procedures. Examples of such monomers are ethylene glycol dimethacrylate (EGDMA), propylene fumarate dimethacrylate (PFDMA), trimethylolpropane triacrylate (TMPTA), EHA, butanediol dimethacrylate (BDMA), glycerol monomethacrylate (GMMA) and hydroxyethylmethacrylate (HEMA), to name a few [ 56 , 57 , 58 ]. For example, EGDMA and PFDMA have been used for the culture of human mesenchymal stem cells (hMSCs).…”
Section: Cell Culturing and Tissue Generation On Polyhipesmentioning
confidence: 99%
“…For example, EGDMA and PFDMA have been used for the culture of human mesenchymal stem cells (hMSCs). Both have been shown to have high cell viabilities of the seeded hMSCs (90% in the case of PFDMA) [ 56 ]. A copolymer made up of EGDMA, PFDMA and BDMA was also shown to have high cell viability for hMSCs [ 57 ].…”
Section: Cell Culturing and Tissue Generation On Polyhipesmentioning
confidence: 99%
“…Whitely M. et al found that high protein loading efficiencies were achieved in porous microspheres. Although there is a short period of explosive release, the protein sustained released with minimal burst release [ 6 ]. Protein is encapsulated into porous microparticles/microscaffolds to avoid the problems caused by traditional preparation methods.…”
Section: Introductionmentioning
confidence: 99%